The Effectiveness of Interactive Digital Media in Increasing Interest in Learning Islamic Religious Education in Secondary Schools - Muhamad Sidiq Asyhari (Al-Ilmu, 2026)
This study aims to analyze the effectiveness of interactive digital media in increasing interest in learning Islamic Religious Education (PAI) in secondary schools. The method used is a quasi-experimental design with Nonequivalent Control Group Design involving 120 grade XI students from MAN 1 Gresik and MAN 2 Gresik, East Java. The sample was divided into an experimental group (60 students) who used interactive digital media and a control group (60 students) who used conventional methods. The research instrument was a learning interest questionnaire with a Likert scale that had been tested for validity (r > 0.361) and reliability (α = 0.892). The results showed that there was a significant difference between students' learning interest in the experimental and control groups (t = 8.457; p < 0.001). The experimental group had an average learning interest score of 74.3 (very high category) compared to the control group of 58.2 (high category). The increase in learning interest in the experimental group reached 27.8% from pretest to posttest. Interactive digital media has been proven effective in increasing students' attention, interest, motivation, and active participation in Islamic Religious Education (PAI) learning. This research provides theoretical and practical contributions to the development of innovative and adaptive PAI learning models in the digital era.